Representasi Ideologi dalam Kaidah Tafsir: Studi Atas Kitab al-QawaÌ„â€™id al-HÌ£isaÌ„n li-TafsiÌ„r Al-Qurâ€™aÌ„n Karya Al-Saâ€™diÌ„ - Fatihullah, Fatihullah (MAGHZA: Jurnal Ilmu Al-Qur’an dan Tafsir, 2018)
This paper discusses al-Qawā’id al-Ḥisān li-Tafsīr al-Qur’anwritten by al-Sa’di, a work with a particular format talking about interpretation rule. The interpretation rules are like a helpful tool to come with the Quran and its interpretation as such that its users can avoid from the mistake and differentiate which one is acceptable and rejected. As a tool to understand the Quran, the interpretation rule is essentially similar with usul fiqh (legal rule) in its formulation that must be scientific (verifiable), critical (non-sectarian) and objective (nonideological). This research proves that the listed rules of interpretation in al-Qawā’id al-Ḥisān li-Tafsīr al-Qur’anare not purely theoretical-objective rules, rather represent al-Sa’di’s ideological and subjective nuances.